1984
DOI: 10.1038/312566a0
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary origin of a calcium-dependent protease by fusion of genes for a thiol protease and a calcium-binding protein?

Abstract: Calcium-dependent protease (calcium protease) is apparently involved in a variety of cellular processes. Here we have attempted to clarify the role and regulatory mechanism of calcium protease by analysing its structure. The complete primary structure of calcium protease (relative molecular mass (Mr) 80,000 (80K), 705 amino acids) was deduced from the nucleotide sequence of cloned complementary DNA. The protein contains four distinct domains, and we have observed a marked similarity between the second and four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
166
0
1

Year Published

1986
1986
2004
2004

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(174 citation statements)
references
References 16 publications
7
166
0
1
Order By: Relevance
“…We had considered it most likely that Sm31 is a h , , 1 . I Study of two Schistosoma mansoni proteins, Sm3l and Sm32 (Barrett et al, 1984), human lysosomal cathepsin B (Chan et al, 1986), S. mansoni Sm31 (Klinkert et al, 1989), chicken calpain (Ohno et al, 1984), Streptococcus pyogenes proteinase (Tai et al, 1976) and S. mansoni Sm32 (Klinkert et al, 1989;El Meanawy et al, 1990), Clostridium histolyticum clostripain (Gilles et al, 1983) and poliovirus 3C proteinase (Argos et al, 1984) are aligned so as to achieve maximal identity ( Figure 6). Cysteine-proteinase-related enzymes found in bacteria are represented by the proteinase of S. pyogenes and clostripain from C. histolyticum.…”
Section: Discussionmentioning
confidence: 99%
“…We had considered it most likely that Sm31 is a h , , 1 . I Study of two Schistosoma mansoni proteins, Sm3l and Sm32 (Barrett et al, 1984), human lysosomal cathepsin B (Chan et al, 1986), S. mansoni Sm31 (Klinkert et al, 1989), chicken calpain (Ohno et al, 1984), Streptococcus pyogenes proteinase (Tai et al, 1976) and S. mansoni Sm32 (Klinkert et al, 1989;El Meanawy et al, 1990), Clostridium histolyticum clostripain (Gilles et al, 1983) and poliovirus 3C proteinase (Argos et al, 1984) are aligned so as to achieve maximal identity ( Figure 6). Cysteine-proteinase-related enzymes found in bacteria are represented by the proteinase of S. pyogenes and clostripain from C. histolyticum.…”
Section: Discussionmentioning
confidence: 99%
“…Domain II is homologous to thiol protease like papain, and domain IV to calcium-binding protein like calmodulin. The origins and functions of domains I and III are, however, unknown [4]. Thus, Ca*+-protease probably arose through the fusion of genes encoding 4 polypeptides with completely different functions [4].…”
Section: Methodsmentioning
confidence: 99%
“…These differences are probably due to the nucleotide sequence polymorphism. to residue -10 of exon 1, the 5'-end of exon 1 shown in parentheses was determined by S1 mapping analysis [16] as described in [4]. The border sequence shown at the splice donor site of exon 21 (in parentheses) represents the 3'-terminus of the gene, namely, the poly(A) addition site, and lower-case letters indicate the sequence which is not transcribed.…”
Section: Subcloning and Dna Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the further alteration of the threonine residue into glycine residue (ST mutant), we obtained cells expressing the unphosphorylated pre-IL-l~. When calpain is converted to an activated form after calcium-dependent translocation to the cell membrane, the calcium-binding domain, the E-F hand structure in calpain, is involved in the calcium-dependent translocation to the cell membrane [24]. It was also reported that cytosolic phospholipase A2 was translocated via a calcium-dependent phospholipidbinding motif [25].…”
Section: Discussionmentioning
confidence: 99%